Reducing antibiotics for respiratory tract symptoms in primary care: consolidating 'why' and considering 'how'. - Butler, C; Rollnick, S; Kinnersley, P; Jones, A; Stott, N (1998)
We summarize recently published evidence showing that antibiotic treatment offers little or no benefit to most patients presenting with sore throats, acute otitis media, maxillary sinusitis, and acute bronchitis. Despite this research, the prescription of antibiotics for respiratory tract conditions is rising in Britain. This wastes money, encourages people to consult for self-limiting conditions, and causes bacteria to become resistant to antimicrobials. Ways of changing present practice are underresearched. Enhanced consulting skills, guidelines and monitoring strategies, patient education, and anti-inflammatory drugs for recurrent and chronic sufferers all hold promise.